2019
DOI: 10.1146/annurev-devpsych-121318-084950
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Adversity and Neural Development: A Systematic Review

Abstract: An extensive literature on childhood adversity and neurodevelopment has emerged over the past decade. We evaluate two conceptual models of adversity and neurodevelopment—the dimensional model of adversity and stress acceleration model—in a systematic review of 109 studies using MRI-based measures of neural structure and function in children and adolescents. Consistent with the dimensional model, children exposed to threat had reduced amygdala, medial prefrontal cortex (mPFC), and hippocampal volume and heighte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
501
6
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 533 publications
(541 citation statements)
references
References 194 publications
(301 reference statements)
27
501
6
7
Order By: Relevance
“…One of the most consistently observed emotional patterns among children with trauma exposure is heightened emotional reactivity, such that salient negative cues in the environment (e.g., angry or fearful faces; social situations depicting people experiencing negative emotions) elicit greater emotional responses in children with trauma histories as compared to children who have never encountered trauma [31,65]. This heightened emotional reactivity has been observed in studies utilizing behavioral tasks, self-report measures, and experience sampling (i.e., ecological momentary assessment) methods [61,[66][67][68] as well as neurobiological responses, including greater activation in the amygdala and anterior insula, brain regions that encode emotional salience, to negative relative to neutral stimuli [69][70][71][72][73]. These patterns have been observed inconsistently in children exposed to other forms of adversity, particularly those involving deprivation [73].…”
Section: Emotional Processing Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most consistently observed emotional patterns among children with trauma exposure is heightened emotional reactivity, such that salient negative cues in the environment (e.g., angry or fearful faces; social situations depicting people experiencing negative emotions) elicit greater emotional responses in children with trauma histories as compared to children who have never encountered trauma [31,65]. This heightened emotional reactivity has been observed in studies utilizing behavioral tasks, self-report measures, and experience sampling (i.e., ecological momentary assessment) methods [61,[66][67][68] as well as neurobiological responses, including greater activation in the amygdala and anterior insula, brain regions that encode emotional salience, to negative relative to neutral stimuli [69][70][71][72][73]. These patterns have been observed inconsistently in children exposed to other forms of adversity, particularly those involving deprivation [73].…”
Section: Emotional Processing Mechanismsmentioning
confidence: 99%
“…This heightened emotional reactivity has been observed in studies utilizing behavioral tasks, self-report measures, and experience sampling (i.e., ecological momentary assessment) methods [61,[66][67][68] as well as neurobiological responses, including greater activation in the amygdala and anterior insula, brain regions that encode emotional salience, to negative relative to neutral stimuli [69][70][71][72][73]. These patterns have been observed inconsistently in children exposed to other forms of adversity, particularly those involving deprivation [73].…”
Section: Emotional Processing Mechanismsmentioning
confidence: 99%
“…The first study to investigate a neural mechanism of stress sensitization found that the association between SLEs and depression symptoms several years later was elevated among participants with high amygdala reactivity (Swartz, Knodt, Radtke, & Hariri, 2015). Heightened amygdala reactivity has been consistently associated with childhood adversity (Hein & Monk, 2017), particularly childhood trauma (McLaughlin, Weissman, & Bitrán, 2019). Thus, amygdala reactivity to threat reflects one potential neural mechanism of stress sensitization to depression.…”
Section: Introductionmentioning
confidence: 99%
“…Reductions in the volume of the hippocampus and amygdala have been consistently observed in children and adolescents exposed to adversity, particularly following exposure to violence (see McLaughlin et al, 2019 for systematic review). Extensive work in animal models demonstrates the toxic and lasting effects of early-life exposure to stress on the hippocampus (Watanabe, Gould, & McEwen, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…We propose that alterations in hippocampal and amygdala volumes are potential mechanisms of stress sensitization. In a recent systematic review, we found that smaller amygdala volume and smaller hippocampal volume are the most consistent differences in brain structure associated with threatrelated adversity in children and adolescents (5). Threatening experiences early in life (e.g., interpersonal violence) may alter amygdala structure and function to promote rapid identification of threats in the environment (6).…”
Section: Introductionmentioning
confidence: 95%